ASYNCHRONOUS LEARNING AS FISHING MANAGEMENT LITERACY IMPROVEMENT ON BAJO TRIBE - misran rahman (Jurnal Pendidikan (Teori dan Praktik), 2022)
This study aims to obtain an overview about the efficacy of implementation of the asynchronous learning to improve literacy skills of the fishermen of Bajo Tribe, a community which built settlement above the sea. Asynchronous model is applied, in response to restricted physical interaction during Covid-19 pandemic and other natural limitations, to improve understanding about marine life. The method used in this research is a workshop plus discussion, with 25 participants. The results showed that most of the respondents realized that the sea has a variety of marine life that is very beneficial for human life. The participants genuinely interested in discovering environmentally sustainable fishing management options, to enrich their awareness and knowledge as well as to improve skills about fishing management. Keywords: Asynchronous learning, education and training, fishing management literacy, Bajo Tribe